Análisis territorial de la cuenca del río Omas (Asia) - Comeca Chuquipul, Miguel Angel (2007)
The sparial planification and lió' too! 10 utilized in our country implicate lo {he hidrograficbasinlike unitslo analysis.ln this investigationcoulddo theanalysis (O the physical. social. economic aspect of the basin tu Omas s river to specially tocare and explain the potentials. the principuls problems aud limitations for example poverty to naturals resource, deticit {O equipment to sen'ice. migra/ion to (he people ami povertypreseut to tlie state. ln this investigation to do emphasis to district to Coayllo.because in this place /0 summarize tlie problematic of the basin.